(untitled) (Research, Society and Development, 2022)
Introduction: considered provocative, “Joker”, the work released in 2019 and directed by Todd Philips, has raised different interpretations regarding the sanity of Arthur Fleck, the failed comedian who transmutes into the Joker. It is an unsettling film, and part of this unrest is due to the coexistence of elements of drama, tragedy, comedy, suspense and psychological terror. Objective: to analyze the provocative and disturbing neuropsychic profile of the character Joker, by Joaquin Phoenix, in the work “Joker”. Methodology: this is a descriptive research of the type narrative review of the literature. Joaquin Phoenix, in the work “Joker”. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases. Information Services. Results and discussion: hypotheses were raised that the character suffers from some neuropsychic disorders, such as gelastic epilepsy, pseudobulbar syndrome, schizophrenia, personality disorder, dissociative identity disorder, trauma disorders, psychopathy and major depressive disorder. Furthermore, extrinsic factors can also corroborate the psychic profile. Final considerations: Joker represents the inexplicable, the incomprehensible, what defies theories and classifications. He is a less psychiatric and more existentialist character in confronting us with the absurdity of evil in the world.